The Influence of Hedonic Motive, Shopping Lifestyle and Religiosity on Customer’s Impulse Buying Behavior: Moderated by Fear of Missing Out - Athar, Handry Sudiartha; Faerrosa, Lady (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
In recent years, there has been significant change in consumer behavior, particularly in the decision-making process and its influence on purchase intentions. Diverse market conditions, characterized by increased competition, have underscored the importance of understanding factors affecting consumer behavior. This study aims to explore the influence of hedonic motives, shopping lifestyle, and religiosity on impulse buying among customers of Muslim fashion stores with Fear of Missing Out (FOMO) as a moderating variable. The research employs a quantitative approach with purposive sampling technique to select 100 Muslim women respondents. Data collection is conducted through online questionnaires and analyzed using Structural Equation Modeling Partial Least Squares (SEM PLS). The findings demonstrate that hedonic motives and shopping lifestyle significantly and positively influence impulse buying, while religiosity also plays a role in enhancing impulsive purchasing behavior. However, FOMO does not significantly moderate the relationship between religiosity and impulse buying. These results highlight the interplay between psychological and cultural factors in shaping consumer behavior in niche markets. The study provides actionable insights for marketers in the Muslim fashion sector to design targeted strategies that resonate with consumer motivations. Additionally, it contributes to the theoretical understanding of consumer behavior within the context of religious and cultural influences, offering a foundation for future research in this domain.